Dejavniki sprejetja celovitih programskih rešitev - Sternad, Simona (Uporabna informatika (Ljubljana), 2012)
Due to their scope and complexity, ERP solutions should receive a lot of attention not only regarding their selection and implementation phases, but also their usage. Although literature frequently states that a successful use of ERP solutions depends on the users, a more detailed review of the topic has revealed that the question concerning the factors which influence the actual adoption and use of ERP solutions has not yet been properly answered. The purpose of this paper is to present the adapted technological acceptance model (TAM) as one of the most widely used models for explaining the behavioural intention and the actual usage of ERP solutions. We adapted this model to explain which factors most fully assess the degree of the ERP usage. These factors are: social influence, business processes fit, user manuals, system performance, data quality, computer anxiety and personal innovativeness toward IT. Apart from the presented model, the paper also identifies the external factors which affect the acceptance and the use of the ERP solutions and indicates theoretical foundations for further applied research based on the findings of our study.
Keywords: corporation; podjetje; poslovni proces; information technology; informacijska tehnologija; informatika; information science; modeli